Morphological Change of Coastal Kampung Kota: Resilience and Vulnerability of Kampung Cungkeng and Sinar Laut, Bandar Lampung, Indonesia - Widya, Amelia Tri; Lestari, A. Dwi Eva; Vividia, Yemima Sahmura; Nurzukhrufa, Antusias; Aziza, Melati Rahmi; Tanjung, Adinda Sekar (The Directorate for Research and Innovation, Institut Teknologi Bandung, 2025)
‘Kampung kota’ (urban villages) in Indonesia represent informal settlements that emerge organically and unplanned, blending urban living with local cultural identities. Despite their unplanned growth and associated risks, such as flooding, fires, and economic instability, these communities exhibit remarkable resilience through strong social ties, adaptive spatial practices, and cultural continuity. Using urban morphology as an analytical lens, this study examined the resilience and vulnerability of Kampung Cungkeng and Sinar Laut, two coastal Bugis settlements in Bandar Lampung. The morphological changes reveal the development patterns and social and economic data integration within their structure. The research was conducted by field observations, in-depth interviews, and spatial analysis by satellite imagery to study the settlements. Their morphological transformations were examined over decades. The findings reveal how physical adaptations, such as stilt houses and mangrove planting, help mitigate vulnerabilities. Additionally, socio-economic strategies like the multifunctional use of space contribute to reducing risks while preserving cultural heritage. However, unregulated expansion and environmental pressures exacerbate risks, highlighting the need for integrated planning. The findings underscore the dual nature of ‘kampung kota’ as both resilient and vulnerable, offering insights for sustainable urban development. The study’s results contribute to the global discourse on informal urban resilience by highlighting how coastal ‘kampung kota’ can contribute to the world discourse on informal urban resilience through unique spatial adaptations and cultural sustainability